PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS III SD NEGERI 011 SIDOREJO KECAMATAN SIMPANG KANAN - Patimah '; Lazim. N '; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The problem in this research is the low learning outcomes IPA Elementary School third-grade students 011 Sidorejo ie with an average of 61.95 with KKM 65. This is because the teacher is still less varied in using models or strategies in the learning process that resulted in the current active students are less involved learn. The study is in the form of classroom action research (PTK). This study aims to improve learning outcomes IPA Elementary School third-grade students 011 Sidorejo. The formulation of the problem "Does the application of the type learning model Numbered Head Together (NHT) can improve learning outcomes IPA third grade students of SD Negeri 011 Sidorejo?". Subjects of this study third grade students of 20 people consisting of 6 men and 14 women. research results show that the activity of teachers has increased by 66.66% in the first cycle to 87.5%. Activities of students also increased by ie from 91.66% to 95.83% in the second cycle. Learning outcomes of students has increased from a base score with an average of 61.95 increased by 62.5% to 75 at UH Cycle I, subsequently at the UH second cycle students on average increased by 87.5% to 95.83%. The completeness classically increased from 59.75% to preliminary data increased to 67.75% in the first cycle, subsequently increased to 80.5%. From these data it can be concluded that the application of the type of learning model Numbered Head Together (NHT) can improve learning outcomes IPA third grade students of SD Negeri 011 Sidorejo.Keywords: Learning Model Type Numbered Head Together (NHT), IPA Learning Outcomes